Acupressure gua sha and massage with kutus-kutus oil accompanied using a stabilization splint in patients with temporomandibular disorder - Maysfera, Nanda Iswa; Ricca Chairunnisa; Haslinda Z Tamin (Indonesia Prosthodontic Association, 2024)
ABSTRACT Background: The most common temporomandibular disorder (TMD) is characterized by disc displacement with reduction (DDWR). Despite its typical signs such as clicking, DDWR has complex symptomatic characteristics, thus; conservative treatment including occlusal splint and physical therapy are commonly performed. Physical therapy, such as acupressure using acupuncture points and massage, is an alternative to DDWR treatment. Objectives: This paper aims to explain the DDWR treatment using stabilization splints and acupressure therapy using gua sha accompanied by a massage with Kutus-Kutus oil. Case report: A 36-years-old male patient arrived at USU Dental Hospital with complaints of clicking right jaw and feeling pain in zygomatic and mandibular area. The patient has been experiencing pain under stress and during periods of high activity for the past six months. This pain is often accompanied by clenching of the jaw, particularly when the patient is worried or concentrating, and the patient tends to sleep on one side. Upon clinical examination, a sound was detected in the right temporomandibular joint (TMJ). The patient was able to open their mouth to a width of 34 mm without experiencing pain, although there was a noticeable deviation to the right. No pain was reported in the joint area during mouth opening. Radiographic examination revealed that the right and left mandibular condyles were positioned anterior to the articular tubercle. For symptomatic treatment, stabilization splints were used in conjunction with physical therapy, which included acupressure gua sha and massage with Kutus-Kutus oil. The use of a stabilization splint caused the patient to experience discomfort during clenching, which gradually led to the cessation of this detrimental habit. This intervention helped to reduce pain and eliminate the clicking sounds associated with TMJ disorder. Conclusion: the combined use of acupressure gua sha, massage with Kutus-Kutus oil, and a stabilization splint can effectively alleviate the pain and clicking symptoms in patients with TMJ disorder. Keywords: TMJ disorder, stabilization splint, acupressure, gua sha, massage